THE IMPLEMENTATION OF ASYLUM SEEKERS DAN REFUGEES LAW ENFORCEMENT IN INDONESIA AFTER PRESIDENTIAL DECREE NUMBER 125 OF 2016 ON THE TREATMENT OF FOREIGN REFUGEES - M. Alvi Syahrin; Yusa Shabri Utomo (Jurnal Ilmiah Kajian Keimigrasian, 2019)
The movement of population was only a domestic issue of a country, but along with the number of countries that paid attention to Asylum Seekers and Refugee so that these issues become worldwide problem. In International law the existence of these refugee protected by the 1951 Refugee Convention and 1967 Refugee Protocol about Refugee. The Indonesian state did not ratify the Protocol so that Indonesia was not obliged to accept the asylum seekers and refugee. However, Indonesia’s strategic position makes Indonesia become a transit country for those who want to continue into the destination country. Therefore, the Government of Indonesia issued a Presidential Decree Number 125 of 2016 concerning Handling of Foreign Refugees. The problem research is how to handling asylum seekers and refugee after the publication of Presidential Decree Number 125 of 2016 concerning Handling of Foreign Refugees. This research is used empirical-normative research methods. Thus, the Government of Indonesia already has a legal basis to handle these asylum seekers and refugees. Indonesia is expected can be more instrumental in addressing the problem of asylum seekers and refugees internationally even thought Indonesia has not ratified the 1951 Convention and the 1967 Protocol. However, in its implementation Presidential Decree Number 125 of 2016 concerning Handling of Foreign Refugees did not run smoothly. It’s because a lot of their handling has not yet referred to the Presidential Regulation.